Evidence of Chikungunya virus seroprevalence in Myanmar among dengue-suspected patients and healthy volunteers in 2013, 2015, and 2018. - Elizabeth Ajema Chebichi Luvai; Aung Kyaw Kyaw; Nundu Sabiti Sabin; Fuxun Yu; Saw Wut Hmone; Kyaw Zin Thant; Shingo Inoue; Kouichi Morita; Mya Myat Ngwe Tun (Public Library of Science (PLoS), 2021)
Introduction Chikungunya virus (CHIKV) is a mosquito-borne virus known to cause acute febrile illness associated with debilitating polyarthritis. In 2019, several institutions in Myanmar reported a CHIKV outbreak. There are no official reports of CHIKV cases between 2011 and 2018. Therefore, this study sought to determine the seroprevalence of CHIKV infection before the 2019 outbreak. Methods A total of 1,544 serum samples were collected from healthy volunteers and patients with febrile illnesses in Yangon, Mandalay, and the Myeik district in 2013, 2015, and 2018. Participants ranged from one month to 65 years of age. Antibody screening was performed with in-house anti-CHIKV IgG and IgM ELISA. A neutralization assay was used as a confirmatory test. Results The seroprevalence of anti-CHIKV IgM and anti-CHIKV IgG was 8.9% and 28.6%, respectively, with an overall seropositivity rate of 34.5%. A focus reduction neutralization assay confirmed 32.5% seroprevalence of CHIKV in the study population. Age, health status, and region were significantly associated with neutralizing antibodies (NAbs) and CHIKV seropositivity (p < 0.05), while gender was not (p = 0.9). Seroprevalence in 2013, 2015, and 2018 was 32.1%, 28.8%, and 37.3%, respectively. Of the clinical symptoms observed in participants with fevers, arthralgia was mainly noted in CHIKV-seropositive patients. Conclusion The findings in this study reveal the circulation of CHIKV in Myanmar's Mandalay, Yangon, and Myeik regions before the 2019 CHIKV outbreak. As no treatment or vaccine for CHIKV exists, the virus must be monitored through systematic surveillance in Myanmar.